Superoxide dismutase in ruminal bacteria. - Fulghum, R S (1984)
Of 13 species of anaerobic ruminal bacteria examined, 11 were found to contain measurable levels of superoxide dismutase activity. Four of five other strict anaerobic species studied for comparison were found to contain superoxide dismutase activity.